Novel components in the nuclear factor-kappa B (NF-κB) signaling pathways of endothelial cells under hyperglycemic-ischemic conditions - Singh, Madhu V.; Wong, Thomas; Moorjani, Sonia; Mani, Arul M.; Dokun, Ayotunde O. (Frontiers in Cardiovascular Medicine, 2024)
Diabetes worsens the outcomes of a number of vascular disorders including peripheral arterial disease (PAD) at least in part through induction of chronic inflammation. However, in experimental PAD, recovery requires the nuclear factor-kappa B (NF-kB) activation. Previously we showed that individually, both ischemia and high glucose activate the canonical and non-canonical arms of the NF-kB pathway, but prolonged high glucose exposure specifically impairs ischemia-induced activation of the canonical NF-kB pathway through activation of protein kinase C beta (PKCβ). Although a cascade of phosphorylation events propels the NF-kB signaling, little is known about the impact of hyperglycemia on the canonical and non-canonical NF-kB pathway signaling. Moreover, signal upstream of PKCβ that lead to its activation in endothelial cells during hyperglycemia exposure have not been well defined. In this study, we used endothelial cells exposed to hyperglycemia and ischemia (HGI) and an array of approximately 250 antibodies to approximately 100 proteins and their phosphorylated forms to identify the NF-kB signaling pathway that is altered in ischemic EC that has been exposed to high glucose condition. Comparison of signals from hyperglycemic and ischemic cell lysates yielded a number of proteins whose phosphorylation was either increased or decreased under HGI conditions. Pathway analyses using bioinformatics tools implicated BLNK/BTK known for B cell antigen receptor (BCR)-coupled signaling. Inhibition of BLNK/BTK in endothelial cells by a specific pharmacological inhibitor terreic acid attenuated PKC activation and restored the IkBa degradation suggesting that these molecules play a critical role in hyperglycemic attenuation of the canonical NF-kB pathway. Thus, we have identified a potentially new component of the NF-kB pathway upstream of PKC in endothelial cells that contributes to the poor post ischemic adaptation during hyperglycemia.